Actuarial Modelling For Diabetes Mellitus Insurance - Fauzan Rafi Amrullah; Mila Kurniawaty; Sa’adatul Fitri (Mathematics Department, Maulana Malik Ibrahim State Islamic University of Malang, 2025)
Diabetes mellitus is a hereditary disease with an increasing number of cases globally and has become one of the leading causes of death from critical illness in Indonesia. Several researchers have highlighted that genetic and social factors play a significant role in the development of diabetes mellitus. Consequently, financial planning and health insurance are essential. Diabetes health insurance is particularly beneficial for individuals with a family history of diabetes mellitus and individuals with unhealthy lifestyles who may become the first carriers to develop the disease. Some researchers have introduced actuarial models for calculating health insurance premiums and reserves, based on compartmental models used in the study of epidemics and pandemics. In this article, we aim to expand on previous research by applying actuarial models to diabetes mellitus model, while incorporating genetic and social factors. We hope that this article can serve as a reference for the public in financial planning, such as participating in insurance programs, to maintain financial stability.